4,4′-Bipyridine-1,1′-diium tetrachloridodifluoridostannate(IV) monohydrate - Amina Kemmouche; Rochdi Ghallab; Hocine Merazig (IUCrData)
In the title hydrated salt, (C10H10N2)[SnF2Cl4]·H2O, the dihedral angle between the pyridinium rings in the cation is 40.5 (4)° and the F atoms in the octahedral complex anion have a cis disposition [F—Sn—F = 85.32 (17)°]. In the extended structure, alternating cationic and anionic layers occur, linked by extensive hydrogen bonding, with water molecules inserted between the layers.